Formation of dimethyl sulfide from the decomposition of S-methylmethionine in tea (Camellia sinensis) during manufacturing process and infusion brewing. (December 2022) - Zhai, Xiaoting; Wang, Jing; Wang, Hui; Xue, Manman; Yao, Xin; Li, Mengru; Yu, Jieyao; Zhang, Liang; Wan, Xiaochun
Graphical abstract: Highlights: Dimethyl sulfide was a key odorant in various teas. Dimethyl sulfide formed from S -methylmethionine during brewing of the tea infusion. Thermal-induced formation of dimethyl sulfide also occurred during the drying step. Abstract: Dimethyl sulfide (DMS) is a typical odorant contributing a cooked corn-like odor to tea ( Camellia sinensis ). In the study, noticeable increases of DMS (>350%) occurred in green, black, yellow, and white tea during brewing. Thermal model and quantitative analysis of S -methylmethionine (SMM) confirmed the thermal decomposition of SMM into DMS (44–80%) in tea infusion. The quantitative analysis on green and black tea manufacturing processes demonstrated thermal decomposition of SMM (12% and 9.0%, respectively) leads to DMS formation during the drying step. Besides, DMS was firstly suggested to be biosynthesed from yet unknown precursors due to high concentrations in fresh leaves (180 and 1700 μg/kg) and increases during rolling (190 and 2800 μg/kg) and fermentation (6400 μg/kg in black tea). The findings provided new insight of DMS formation from the decomposition of SMM in tea during manufacturing process and infusion brewing, which also help exploring its biosynthetic pathway during tea production.